Developing a Contextual Framework for Land Value Capture in Lagos, Nigeria - Famuyiwa, Funlola (Journal of African Real Estate Research, 2022)
This study aims at developing a framework to guide the use of Land Value Capture (LVC) as a financing mechanism for infrastructure development in Lagos State, Nigeria. This is geared towards facilitating sustainable economic development in the region. Being a desk research, the methodology adopted was a literature survey. This was in order to identify baseline conditions necessary for the efficient application of LVC. The conditions identified, were then analyzed in terms of their workability within the context of the study area. Data was drawn from research articles, case studies, policy papers, and publications from relevant intergovernmental organizations. In addition to developing a framework, which guides the use of LVC in the study area, the study found that there is potential for the application of LVC in Lagos. Areas requiring minimal intervention include the existence of a vibrant property market and lead implementing institution. The state’s current inability to fully capitalize on LVC, are in the areas of having a strategic national vision, a clear policy framework, sound structure for institutional development finance, and an effective land title documentation system. This is the first study that develops a framework for the use of LVC specifically for Lagos. Further, the paper contextualizes the baseline conditions for LVC in Lagos, Nigeria, presenting an alternate finance mechanism for infrastructure development revenue in the region.